Evaluating the performance of teachers of philosophy and psychology of the preparatory stage according to the competencies of the effective teacher - al-Maliki, Hamid Qasim Ghadban (Al-Adab Journal, 2020)
Throw your search calendar school philosophy performance and the psychology of the preparatory phase according efficiencies of effective teacher, and to achieve the goal of research, the researcher note form containing (30) the adequacy of distributed (3) areas, has been to ensure the veracity of the research and persistence tool, where this tool applied Find a sample consisting of (109) as a teacher and a school, and the researcher used appropriate statistical methods to complete his research, the results showed that the level of availability of competencies for effective teacher at the school of philosophy and psychology was considered accrued incredibly good.